Winner the diamond award in the International Innovation and Invention Competition (INIIC 2/2019 series) - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2020)
Pn Mariam Mahmun (AAGBS DBA Part 4 student from UiTM Sabah) Assoc Prof Dr Imbarine Bujang & Mr Ahmad Fauze Abdul Hamit.